PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL (Studi Pada Perusahaan Yang Terdaftar Di Forum Corporate Governance Indonesia (FCGI) Tahun 2011-2014) - Faizal Mochamad, 11.05.52.0135; Indarti, MG Kentris (Students Journal of Accounting and Banking, 2016)
This research aims to determine and analyze the influence of corporate governance, profitability, leverage, company size, and age of company on the intellectual capital disclosure.Â This research was conducted at the companies that are registered in the Corporate Governance Perception Index (CGPI) in the 2011-2014 periods with the total 136 observations, 4 years for the data observation and the selected companies to be sampled in this research are 66 companies. The used of sampling technique is purposive sampling. The data analysis is multiple linear regressions.Â The results of this research showed that each variable had different effect depending which indicates that the variable CGPI positive effect was not significant to the disclosure of intellectual capital, Profitability significant negative effect on the intellectual capital disclosure, leverage significant positive effect on the intellectual capital disclosure, company size effect negative not significant to the intellectual capital disclosure, Age of company significant negative effect on the intellectual capital disclosure.Keywords: Intellectual Capital Disclosure, Corporate Governance, Profitability, Leverage, Company Size, Age Of Company